Ethics of intelligence : a new framework - Bellaby, Ross, 1984- (London : Routledge, 2014)
'This book starts from the proposition that the field of intelligence lacks any coherent or systematic ethical review, and then develops an ethical framework for intelligence based on the notion of harm and the establishment of the Just Intelligence Principles. This book argues that the most appropriate ethical framework for intelligence collection is one which is able to recognise that intelligence collection does indeed cause harm, but that sometimes this harm is necessary in order to protect the political community. It tackles this tension by creating an ethical framework specifically designed for intelligence that is able to balance the need to limit the damage caused while securing the political community. This is achieved by developing an ethical framework of two parts. The first part is designed to recognise those features of intelligence that might be considered ethically unacceptable by highlighting the'harm' it can cause. Once the harm is understood, the second part of the ethical framework establishes a set of Just Intelligence Principles that outline if and when the harm caused is justified. These Just Intelligence Principles are developed by drawing upon the just war tradition and its criteria of just cause, legitimate authority, right intention, last resort, proportionality and discrimination. By placing the harm that intelligence can cause into context of the Just Intelligence Principles it is possible to ensure that intelligence collection is only carried out when the circumstances demonstrate a suitable level of threat, authorised by a sufficient level of authority, carrying a right intention, that the damage is proportional to the expected information gains, and discriminates between legitimate and illegitimate targets. The main feature of the ethical framework created, however, is that it recognises that different intelligence collection activities can cause different levels of harm and that as a result the circumstances needed to justify them must also change. The book examines three of the main collection disciplines in the field of intelligence studies: imagery intelligence, signals intelligence and human intelligence. By applying the ethical framework established at the beginning of the book to these three important intelligence collection disciplines, it is possible to better understand the ethical framework while also demonstrating its real-life applicability. This book will be of much interest to students of intelligence studies, ethics, war and conflict studies, security studies and IR'--
'This book starts from the proposition that the field of intelligence lacks any systematic ethical review, and then develops a framework based on the notion of harm and the establishment of Just Intelligence Principles. As the professional practice of intelligence collection adapts to the changing environment of the twenty-first century, many academic experts and intelligence professionals have called for a coherent ethical framework that outlines exactly when, by what means and to what ends intelligence is justified. Recent controversies, including reports of abuse at Guantanamo Bay and Abu Ghraib, allegations of extraordinary rendition programmes and the ever-increasing pervasiveness of the'surveillance state', have all raised concerns regarding the role of intelligence in society. As a result, there is increased debate regarding the question of whether or not intelligence collection can be carried out ethically. The Ethics of Intelligence tackles this question by creating an ethical framework specifically designed for intelligence that is capable of outlining under what circumstances, if any, different intelligence collection activities are ethically permissible. The book examines three of the main collection disciplines in the field of intelligence studies: imagery intelligence, signals intelligence and human intelligence. By applying the ethical framework established at the beginning of the book to these three important intelligence collection disciplines, it is possible to better understand the ethical framework while also demonstrating its real-life applicability. This book will be of much interest to students of intelligence studies, ethics, war and conflict studies, security studies and IR'--
Includes bibliographical references : pages 173-186 and index.
Keywords: Intelligence service -- Moral and ethical aspects; Electronic surveillance -- Moral and ethical aspects; Electronic intelligence -- Moral and ethical aspects; Espionage -- Moral and ethical aspects; Military interrogation -- Moral and ethical aspects -- United States; Torture -- Moral and ethical aspects; Spies -- Professional ethics; Intelligence service -- Moral and ethical aspects -- United States; Terrorism -- Prevention -- Moral and ethical aspects; Privacy -- Moral and ethical aspects